Non-invasive and invasive determinations of the individual anaerobic threshold in competitive swimmers - Harrison, J. R.; Dawson, B. T.; Lawrence, S.; Blanksby, B. A. (Journal of Swimming Research, 1992)
The purpose of this study was to determine if a non-invasive HR protocol is a suitable method of determining the IAnT in swimmers. The two methods (a) Cellini et al. 10-15 x 50 m with successively increasing speeds, and (b) 4-5 300 m swims with each 50 m improving in speed by 1 s each repetition. Implication: It is necessary to have the pace of the total swim controlled to replicate exact conditions when using either HR or HLa as indexes of work. Heart rates cannot be used reliably or accurately to estimate the severity of work loads.